Soviet Policy in Relation to Turkey and South Caucasus in 1920-1921 - E. N. Emelyanova (Научный диалог, 2018)
On the basis of archival documents, little-known facts in the relations between the Soviet state, the Comintern and the government of M. Kemal during the formation of the Russian and Turkish republics are considered. The policy of the Bolshevik power and the role of the Communist Internationale in establishing relations with the national movement of Turkey are analyzed. Considerable attention is paid to the question of the Bolsheviks’ search for allies among the various political forces of Turkish society. The author raises the problem of contradictions between the guidelines of The Council of People’s Commissars aimed at cooperation and interaction with the government of M. Kemal, and unreasonable leftist aspirations of radical elements in the Comintern and the Turkish Communist party. It is noted that the topic of political and military cooperation between Soviet Russia and Turkey is inextricably linked with the policy of both states in the Caucasus, which could become a bridge or a barrier between the two countries. The activity of both states in this region and the role of the Comintern in expanding the influence of Soviet Russia in the republics of Transcaucasia are traced. The urgency of the problem is determined by the need to establish relations with the countries of the Middle East at the present stage, the search for mechanisms of interaction and the use of positive experience and taking into account the mistakes of the past in this matter. The author comes to the conclusion that despite the ideological differences and the clash of political interests, Soviet Russia and Turkey were able to find a compromise and concluded an equal and mutually beneficial peace treaty, which marked the beginning of cooperation between the two countries.